Meaning and Translation - Nugroho, Andy Bayu (Journal of English and Education (JEE), 2007)
Translation is an effort of finding equivalent meaning of a text into the second language. We emphasis meaning equivalence since in translation meaning is the object to be rendered from the source language text into the target language text. In this case, translator is faced with a text as units of meaning in the form of sets of words or sentences.The main question in translation is of meaning which always appears in the process of translation, not translation as a product of the process. Translating a text from the source text(ST) must consider the closest natural equivalent meaning, it implies that the meaning of the target text must be equivalent with that of the source.Meaning is classified into two kinds, referential meaning and connotative meaning. A translator must be aware of which meaning is possibly intended by the author.  Beside, it should also be paid attention on the components embedded in a certain unit of meaning. By understanding the components of meaning of the source language expressions a translator can make the best decision related to the components.